Multimodality imaging: Bird’s eye view from the European Society of Cardiology Congress 2019 Paris, August 31st–September 4th, 2019 - Delgado V.; Saraste A.; Dweck M.; Bucciarelli-Ducci C.; Bax J. (Springer, 2025)
At the European Society of Cardiology (ESC) congress of this year 2019, held in Paris from August 31st to September 4th, 4509 abstracts were presented. Of those, 414 (9%) belonged to an imaging category. Experts in echocardiography (VD), nuclear imaging (AS), cardiac computed tomography (CT) (MD) and cardiovascular magnetic resonance (CMR) (CBD), have selected the abstracts in their areas of expertise that were of most interest to them and are summarized in this bird’s eye view from this ESC meeting. These abstracts were integrated by one of the Editors of the Journal (JB).